FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI DAN PENDAPATAN USAHATANI JAGUNG DI DESA MOJOREJO KECAMATAN JUNREJO KOTA BATU (Agridevina : Berkala Ilmiah Agribisnis, 2022)
This study aims to analyze the factors that affect the production and income of corn farming in Mojorejo Village, Junrejo District, Batu City. The location of this research was carried out in Mojorejo Village, Junrejo District, Batu City. The sampling technique used was random sampling method. The total population is 40 corn farmers with sample size taken using the slovin formula. Data analysis techniques used to determine the factors that affect corn farming production in this study used multiple regression models and income analysis. The results showed that the factors that affected corn production in Mojorejo Village, Junrejo District, Batu City which had a significant effect on corn production (Y) were seeds (X2), organic fertilizer (X3), and liquid fertilizer (X4). Variables that have no significant effect on corn production (Y) are land area (X1), labor (X5), education (X6), age (X7), experience (X8) and family dependents (X9). The income received from corn farming in Mojorejo Village, Junrejo District, Batu City is Rp. 11,453,398,96/planting season (MT) with an average land area of ​​0.45 Ha. DOI : https://doi.org/10.33005/agridevina.v11i2.3370